Rats in the city : implications for zoonotic disease risk in an urbanizing world - Blassdell, Kim R.; Morand, Serge; Laurance, Susan G.W.; Doggett, Stephen L.; Hahs, Amy; Perera, David; Cadhla, Firth (Cold Spring Harbor Laboratory, 2021)
Urbanization is rapidly transforming much of Southeast Asia, altering the structure and function of the landscape, as well as the frequency and intensity of the interactions between people, animals, and the environment. In this study, we began to explore the impact of urbanization on zoonotic disease risk by simultaneously characterizing changes in the abundance and diversity of reservoir hosts (rodents), ectoparasite vectors (ticks), and microbial pathogens across a gradient of urbanization in Malaysian Borneo. We found that although rodent species diversity decreased with increasing urbanization, two species appeared to thrive in anthropogenic environments: the invasive urban exploiter, Rattus rattus and the native urban adapter, Sundamys muelleri. R. rattus was strongly associated with the presence of built infrastructure across the gradient and dominated the urban rodent community where it was associated with high microbial diversity and multi-host zoonoses capable of environmental transmission, including Leptospira spp., and Toxoplasma gondii. In contrast, S. muelleri was restricted to sites with a significant vegetative component where it was found at high densities in the urban location. This species was strongly associated with the presence of ticks, including the medically important genera Ambylomma, Haemaphysalis, and Ixodes. Overall, our results demonstrate that the response to urbanization varies by species at all levels: host, ectoparasite, and microbe. This may lead to increased zoonotic disease risk in a subset of environments across urban and urbanizing landscapes that can be reduced through improved pest management and public health messaging.